Patient journey mapping to investigate quality and cultural safety in burn care for Aboriginal and Torres Strait Islander children and families – development, application and implications - Sarah Fraser; Tamara Mackean; Julian Grant; Kate Hunter; Courtney Ryder; Janet Kelly; Andrew J. A. Holland; Bronwyn Griffin; Kathleen Clapham; Warwick J. Teague; Anne Darton; Rebecca Q. Ivers (BMC Health Services Research, 2022)
Abstract Background Quality and safety in Australian healthcare is inequitably distributed, highlighted by gaps in the provision of quality care for Aboriginal and Torres Strait Islander children. Burns have potential for long-term adverse outcomes, and quality care, including culturally safe care, is critical to recovery. This study aimed to develop and apply an Aboriginal Patient Journey Mapping (APJM) tool to investigate the quality of healthcare systems for burn care with Aboriginal and Torres Strait Islander children. Study design Interface research methodology, using biomedical and cultural evidence, informed the modification of an existing APJM tool. The tool was then applied to the journey of one family accessing a paediatric tertiary burn care site. Data were collected through yarning with the family, case note review and clinician interviews. Data were analysed using Emden’s core story and thematic analysis methods. Reflexivity informed consideration of the implications of the APJM tool, including its effectiveness and efficiency in eliciting information about quality and cultural safety. Results Through application of a modified APJM tool, gaps in quality care for Aboriginal and Torres Strait Islander children and families were identified at the individual, service and system levels. Engagement in innovative methodology incorporating more than biomedical standards of care, uncovered critical information about the experiences of culturally safe care in complex patient journeys. Conclusion Based on our application of the tool, APJM can identify and evaluate specific aspects of culturally safe care as experienced by Aboriginal and Torres Strait Islander peoples and be used for quality improvement.